Sputum basophils are increased in eosinophilic asthma compared with non‐eosinophilic asthma phenotypes. Issue 10 (1st June 2017) - Brooks, C. R.; van Dalen, C. J.; Hermans, I. F.; Gibson, P. G.; Simpson, J. L.; Douwes, J.
Abstract: Sputum basophil numbers are increased in allergic asthmatics, but it is unclear what role airway basophils play in "TH2‐low" asthma phenotypes. Using flow cytometry, we found that basophils were significantly increased in all asthmatics (n=26) compared with healthy controls (n=8) ( P =0.007) with highest levels observed in eosinophilic asthma (EA); median 0.22%, IQR 0.11%‐0.47%; n=14) compared with non‐EA (NEA) (0.06%, 0.00%‐0.20%; n=12; P <0.05). In asthmatics, basophils were positively correlated with sputum eosinophils ( r =0.54; P <0.005) and inversely with sputum neutrophils ( r =−0.46: P <0.05), but not with FEV1 (% predicted), FEV1 /FVC or bronchodilator reversibility. In a subgroup initially identified as inadequately controlled asthma (n=7), there was a trend ( P =0.08) towards a reduction in sputum basophils following increased inhaled corticosteroid (ICS) treatment. Our findings suggest that basophils may be particularly important in eosinophilic asthma and that sputum basophil assessment could be a useful additional indicator of "TH2‐high" asthma.